Differential causes of masticatory muscle disorders in dogs: a review of diagnosis, treatment and long-term management - Fisher, Rachelle; Goldschmidt, Stephanie; Knipe, Marguerite F.; Soltero-Rivera, Maria; Vapniarsky, Natalia; Arzi, Boaz (Frontiers in Veterinary Science, 2026)
Masticatory muscle disorders in the dog are complex and challenging cases to manage. Patients may present with inability or difficulties in opening or closing the mouth, making dysphagia and respiratory compromise major concerns. Time is of the essence in these circumstances, and prompt and accurate diagnosis and treatment are required to prevent potentially life-threatening complications from occurring. Several local and systemic disease processes may cause masticatory muscle dysfunction further complicating the diagnostic process. Current literature on masticatory muscle disorders is widespread with many recommendations in veterinary medicine extrapolated from human medicine. The goal of this paper is to synthesize the current literature and illuminate areas that require additional research.